Autonomy is a Right, Not a Feat: How Theoretical Misconceptions have Muddled the Debate on Dynamic Consent to Biobank Research. (16th March 2016) - Johnsson, Linus; Eriksson, Stefan
Abstract: Should people be involved as active participants in longitudinal medical research, as opposed to remaining passive providers of data and material? We argue in this article that misconceptions of 'autonomy' as a kind of feat rather than a right are to blame for much of the confusion surrounding the debate of dynamic versus broad consent. Keeping in mind two foundational facts of human life, freedom and dignity, we elaborate three moral principles – those of autonomy, integrity and authority – to better see what is at stake. Respect for autonomy is to recognize the other's right to decide in matters that are important to them. Respect for integrity is to meet, in one's relationship with the other, their need to navigate the intersection between private and social life. Respect for authority is to empower the other – to help them to cultivate their responsibility as citizens. On our account, to force information onto someone who does not want it is not to respect that person's autonomy, but to violate integrity in the name of empowerment. Empowerment, not respect for autonomy, is the aim that sets patient‐centred initiatives employing a dynamic consent model apart from other consent models. Whether this is ultimately morally justified depends on whether empowerment ought to be a goal of medical research, which is questionable.